IMPACT OF CERTAIN EDUCATIONAL INTERVENTIONS ON ADVERSE DRUG REACTION REPORTING BY NURSING HEALTH PROFESSIONALS AT A TERTIARY CARE HOSPITAL - SONOWAL, SUPRIYA; K DESAI, CHETNA; R PANCHAL, JIGAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of the study were to evaluate the impact of certain educational interventions on adverse drug reaction (ADR) reporting by nursing health professionals at a tertiary care hospital. Methods: Knowledge, attitude, and practice (KAP) of the nurses regarding ADR reporting were evaluated before and after interventions using a KAP questionnaire. Educational interventions carried out among the nurses were workshops, booklets, SMSes, personal briefings, and posters. Number and quality of ADR reported by nurses in pre-intervention (3 months), intervention (10 months), and post-intervention (3 months) phase were compared. Results: There was a significant increase in response rate to questionnaires in the post-intervention phase (post-IP) (97.74%) as compared to pre-intervention (91.28%) phase (pre-IP). The knowledge score of the nurses increased significantly in post-IP (11.65 ± 2.14) as compared to the pre-intervention (6.98 ± 2.46) phase. No ADR was reported by nurses in pre-IP. Thirty nurses reported 30 ADRs in the intervention phase and six nurses reported six ADRs in the post-IP. The mean score of completeness of ADR notification forms decreased significantly in post-IP. Maximum ADRs (10) were reported after the workshops. Conclusion: Educational interventions improved the KAP of ADR reporting by nurses, albeit temporary. This suggests the need of continuous educational interventions.